Le développement de la lecture orale chez l'enfant. - Desrochers, Alain; Kirby, John; Thompson, Glenn (Canadian Psychology, 2008)
In this paper the authors examine the early development of oral reading of French in children. The authors trace the origin of the French alphabet and provide an overview of the skills that support oral reading development. The authors then distinguish two broad cognitive components of oral reading, analytic and lexical processes, and discuss how they develop with reading practise. Reprinted by permission of the publisher.